A porous graphene oxide composite nanofiltration membrane and a preparation method and application thereof

CN122955368APending Publication Date: 2026-10-23GUANGDONG ESQUEL TEXTILES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611196006.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,上述专利并未对氧化石墨烯进行造孔处理,氧化石墨烯膜的通量虽然较传统有机膜有所提升,但仍然处于较低水平,导致膜运行成本偏高,仍需进一步大幅提升氧化石墨烯膜通量

Benefits of technology

本发明通过对氧化石墨烯进行造孔,形成具有纳米孔的多孔氧化石墨烯,使得水分子可以通过而染料等大分子难以通过,从而在仅小幅降低染料截留率的同时大幅提高膜的通量;同时通过交联剂对多孔氧化石墨烯膜进行离子交联和/或化学交联,提升多孔氧化石墨烯层与层之间的结合力,抑制多孔氧化石墨烯膜的水溶效应,提高膜的结构和化学稳定性。本发明将氧化石墨烯造孔与提升交联程度联用,造孔提升通量、交联提升截留和稳定性,二者协同作用,可以在保持甚至小幅提高染料截留率的同时,大幅提升通量,同时进一步提高GO膜的稳定性。因此,本发明开发了一种制备简单、易批量生产、多孔氧化石墨烯的层间结构稳定、多孔氧化石墨烯膜和基膜之间结合力优良、高通量且具有优异的盐/染料分离性能的氧化石墨烯复合纳滤膜,可应用于含染料的高盐染料废水的处理、含盐染料的脱盐纯化等领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of porous graphene oxide composite nanofiltration membrane and its preparation method and application, belong to nanofiltration membrane technical field.The porous graphene oxide composite nanofiltration membrane includes: base film and the porous graphene oxide film formed on the surface of the base film;The porous graphene oxide film contains porous graphene oxide, and the porous graphene oxide film is formed on the surface of the base film by crosslinking agent in the form of crosslinking;The porous graphene oxide is prepared by pore-forming agent to graphene oxide, and the pore-forming agent includes main pore-forming agent and selectively includes auxiliary agent, and the main pore-forming agent is hydrogen peroxide.The structure of the porous graphene oxide composite nanofiltration membrane of the application is stable, and the separation performance of composite nanofiltration membrane is excellent, and the flux is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a porous graphene oxide composite nanofiltration membrane, its preparation method and application, belonging to the field of nanofiltration membrane technology. Background Technology

[0002] The processing, weaving, and dyeing of cotton textile products are highly complex, with each process adding and generating different pollutants. In particular, the wastewater discharged from the dyeing stage contains large amounts of salts (typically including one or more of NaCl, Na2CO3, and Na2SO4), undyed dyes, and their hydrolysis products. This dyeing wastewater is high in salinity and color, making it difficult to treat biologically. Traditional methods treat this wastewater by mixing it with wastewater from other production stages, diluting the salinity and color, and then subjecting it to advanced treatment through physicochemical, biological, or combined physicochemical-biological methods before discharging it to meet standards. Even after meeting discharge standards, the wastewater still requires advanced oxidation or activated carbon adsorption for complete decolorization to meet reuse requirements. However, these steps inevitably lead to secondary environmental pollution.

[0003] Furthermore, the dyes used in the dyeing process of cotton textile products are reactive dyes, which are typically composed of dye matrix, reactive groups, linking groups, and leaving groups. The production of reactive dyes involves coupling and diazo reactions, during which a large amount of acid is added to adjust the pH, ultimately neutralizing to form salts. In addition, many reaction intermediates are of low purity and contain a large amount of salt. Therefore, the final synthesized dye contains a large amount of salt, unreacted intermediates, and reaction byproducts. Traditional cotton textile dyeing processes add electrolytes, so impurities such as salt in the dye do not significantly affect the dyeing process. However, with increasing environmental awareness, digital printing and non-aqueous dyeing of cotton textile products are gradually developing. Unlike traditional dyeing processes, digital printing uses reactive dyes to formulate printing inks, which have strict requirements on the salt content of the dyes; otherwise, it will cause inkjet nozzle clogging. Non-aqueous dyeing also has very high requirements on the salt content of the dyes; otherwise, it will lead to severe internal and external color differences. Therefore, it is necessary to desalt and purify reactive dyes to prepare high-purity salt-free dyes.

[0004] Loose nanofiltration is a membrane separation technology with pore sizes between ultrafiltration and nanofiltration. While ensuring high retention of organic dyes, it allows most inorganic salts to permeate, thus achieving efficient separation of organic dyes / salt water in dyeing and printing wastewater. It can also be applied to dye desalination and purification, possessing high economic value and research significance. However, most commercial nanofiltration membranes are organic membranes. Due to the inherent properties of polymer network structures, organic membranes have relatively wide pore sizes, poor selectivity, and poor fouling resistance. When treating high-salinity, high-color wastewater or desalinizing and purifying dyes, if a high dye retention rate is required, the organic membrane needs a smaller pore size. In this case, it also retains a certain amount of salt. Due to the osmotic pressure of this retained salt, the membrane flux is very low, making it difficult to simultaneously achieve high flux and dye retention rates.

[0005] Graphene oxide is a derivative of graphene and a single-layer, two-dimensional sheet-like carbon material. Recent studies have shown that water molecules can flow rapidly on the surface of graphene oxide, resulting in excellent separation performance. The surface of graphene oxide is rich in oxygen-containing functional groups such as hydroxyl, carboxyl, epoxy, and carbonyl groups, exhibiting good hydrophilicity. Therefore, it is easily dispersed in water to form a uniform dispersion, making it easy to prepare graphene oxide films.

[0006] Currently, graphene oxide nanofiltration membranes can be prepared using methods such as vacuum filtration, dip coating, spraying, layer-by-layer self-assembly, and coating, exhibiting excellent salt / dye separation performance. CN110523297A discloses a graphene oxide composite nanofiltration membrane and its preparation method. This preparation method includes the following steps: uniformly coating a graphene oxide dispersion onto one side of a base membrane using a coating rod, followed by drying and partial reduction under ultraviolet light irradiation to obtain the graphene oxide composite nanofiltration membrane. CN116020286A discloses a graphene oxide composite nanofiltration membrane, its preparation method, and its application. A mixture containing graphene oxide-like materials, polymer nanomaterials, and a crosslinking agent is coated onto the surface of a base membrane, and a crosslinking reaction is carried out to obtain the graphene oxide composite nanofiltration membrane.

[0007] While the two patents mentioned above provide preliminary solutions for the mass production of graphene oxide nanofiltration membranes, and CN116020286A achieves chemical cross-linking between graphene oxide layers by embedding polymer nanomaterials into the graphene oxide sheets using a cross-linking agent, thus improving the structural and chemical stability of the membrane, CN116020286A also preferentially uses positively charged modified nylon microfiltration membranes as the base membrane, utilizing the electrostatic attraction between the positive charge on its surface and the negatively charged graphene oxide to enhance the bonding force between the graphene oxide membrane and the base membrane. However, these patents do not perform pore-forming treatment on the graphene oxide. Although the flux of the graphene oxide membrane is improved compared to traditional organic membranes, it is still at a relatively low level, resulting in high membrane operating costs. Further significant improvements in the flux of graphene oxide membranes are still needed.

[0008] Therefore, developing a high-flux graphene oxide composite nanofiltration membrane that is simple to prepare, easy to mass-produce, has a stable interlayer structure of graphene oxide, excellent bonding between the graphene oxide membrane and the base membrane, and excellent salt / dye separation performance has become one of the urgent problems to be solved in this field. Summary of the Invention

[0009] To address the aforementioned technical problems, the present invention aims to provide a porous graphene oxide composite nanofiltration membrane, its preparation method, and its applications. The porous graphene oxide composite nanofiltration membrane of the present invention exhibits stable structure, excellent separation performance, and high flux.

[0010] To achieve the above objectives, a first aspect of the present invention provides a porous graphene oxide composite nanofiltration membrane, comprising: a base membrane, and a porous graphene oxide membrane formed on the surface of the base membrane; the porous graphene oxide membrane contains porous graphene oxide, and the porous graphene oxide membrane is formed on the surface of the base membrane by crosslinking through a crosslinking agent; the porous graphene oxide is obtained by creating pores in the graphene oxide using a pore-forming agent, the pore-forming agent comprising a main pore-forming agent and selectively comprising an auxiliary agent, wherein the main pore-forming agent is hydrogen peroxide.

[0011] A second aspect of the present invention provides a method for preparing the above-mentioned porous graphene oxide composite nanofiltration membrane, comprising the following steps: A mixture containing porous graphene oxide and a crosslinking agent is coated onto the surface of a base membrane to carry out a crosslinking reaction, forming a porous graphene oxide membrane, thus obtaining the porous graphene oxide composite nanofiltration membrane.

[0012] The third aspect of this invention provides the application of the above-mentioned porous graphene oxide composite nanofiltration membrane in the treatment of high-salt wastewater containing dyes and / or the desalination and purification of salt-containing dyes.

[0013] The present invention has at least the following beneficial effects: This invention creates porous graphene oxide with nanopores by creating pores in the graphene oxide membrane. This allows water molecules to pass through while preventing the passage of large molecules such as dyes, thereby significantly increasing the membrane flux while only slightly reducing the dye rejection rate. Simultaneously, crosslinking agents are used to ionically and / or chemically crosslink the porous graphene oxide membrane, enhancing the bonding force between the porous graphene oxide layers, suppressing the water solubility effect, and improving the membrane's structural and chemical stability. This invention combines graphene oxide pore-forming with increased crosslinking; pore-forming increases flux, while crosslinking improves rejection and stability. The synergistic effect of these two methods can significantly increase flux while maintaining or even slightly increasing the dye rejection rate, and further improve the stability of the GO membrane. Therefore, this invention develops a graphene oxide composite nanofiltration membrane that is simple to prepare, easy to mass-produce, has a stable interlayer structure of porous graphene oxide, excellent bonding between the porous graphene oxide membrane and the base membrane, high throughput, and excellent salt / dye separation performance. It can be applied to the treatment of high-salt dye wastewater containing dyes, desalination and purification of salt-containing dyes, and other fields. Detailed Implementation

[0014] To provide a clearer understanding of the technical features, objectives, and beneficial effects of the present invention, the present invention will now be described in detail below, but this should not be construed as limiting the scope of the invention.

[0015] It should be noted that, unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0016] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0017] It should be understood that the terms “comprising,” “including,” and / or “containing” as used herein specify the presence of the stated features, integers, steps, components, or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, components, or combinations thereof.

[0018] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0019] According to a specific embodiment of the first aspect of the present invention, the present invention provides a porous graphene oxide composite nanofiltration membrane, comprising: a base membrane, and a porous graphene oxide membrane formed on the surface of the base membrane; the porous graphene oxide membrane contains porous graphene oxide, and the porous graphene oxide membrane is formed on the surface of the base membrane by crosslinking through a crosslinking agent; the porous graphene oxide is obtained by creating pores in the graphene oxide using a pore-forming agent, the pore-forming agent comprising a main pore-forming agent and selectively comprising an auxiliary agent, wherein the main pore-forming agent is hydrogen peroxide.

[0020] Graphene oxide is mainly divided into sp 2 Graphene regions and sp 3 Graphene oxide regions. Graphene oxide films formed by the stacking or self-assembly of graphene oxide layers have a narrow interlayer spacing, which can effectively trap dyes while allowing most salts to pass through, offering unique advantages in salt and dye separation. However, the interlayer bonding force of graphene oxide mainly relies on sp... 2 The π-π conjugation effect in the region means that the bonding force between the graphene oxide film and the base film mainly relies on the hydrogen bonds and van der Waals forces between the graphene oxide and the base film at the phase contact. When the film is in a dry state, the interlayer bonding force of the graphene oxide is good, and there is also a certain bonding force between the graphene oxide and the base film. The better the hydrophilicity of the base film, the better the bonding force between the base film and the graphene oxide film. For example, the bonding force between the graphene oxide film and the nylon base film is good, but the bonding force with the PVDF base film is poor.

[0021] However, due to the water-soluble effect of graphene oxide, when the graphene oxide film comes into contact with water, the carboxyl and hydroxyl groups on the graphene oxide will undergo hydration with the water, causing the interlayer expansion. 2 The π-π conjugation effect in the region weakens or even disappears, resulting in weaker interlayer bonding in the graphene oxide film. Furthermore, the van der Waals forces of the hydrophilic groups between the graphene oxide film and the base film are significantly reduced, further weakening the bonding between them. Therefore, under the influence of water flow or external forces, the graphene oxide film is prone to localized damage, and may even detach directly from the base film. In practical applications, it has also been observed that in the early stages of membrane element fabrication or testing, the graphene oxide film may partially detach from the base film, leading to a lower dye rejection rate for the membrane element compared to the membrane sheet.

[0022] This invention utilizes chemical etching to create pores in graphene oxide sheets, expanding defects into 0.5-2 nm nanopores to obtain porous graphene oxide. Water molecules can pass through, while large molecules such as dyes cannot, thus significantly increasing the flux of graphene oxide while only slightly reducing dye rejection. Furthermore, this invention enhances the interlayer bonding of porous graphene oxide by performing ionic and / or chemical crosslinking, suppressing the water solubility effect of the porous graphene oxide film and improving its structural and chemical stability. However, while high crosslinking of porous graphene oxide can significantly increase rejection, it also significantly reduces flux. This invention combines pore creation and increased crosslinking in graphene oxide. Pore creation increases flux, while crosslinking improves rejection and stability. The synergistic effect of these two methods can significantly increase flux while maintaining or even slightly increasing dye rejection, and further improve the stability of the GO film.

[0023] In some embodiments, the pore-forming agent includes one or more of a strong oxidizing agent, an inorganic base, an organic base, and a ferrous salt. Preferably, the strong oxidizing agent includes one or more of sodium hypochlorite, ozone, and potassium permanganate. Preferably, the inorganic base includes NaOH and / or ammonia. Preferably, the organic base includes C6-C12 tertiary amine compounds. More preferably, the organic base includes one or more of triethylamine, tripropylamine, and tributylamine. Preferably, the ferrous salt includes ferrous sulfate and / or ferrous chloride.

[0024] In some embodiments, during the process of preparing porous graphene oxide by creating pores in graphene oxide with a pore-forming agent, the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, preferably (3-20):1.

[0025] In some embodiments, the sheet size of the graphene oxide is 0.5-100 μm, preferably 3-10 μm.

[0026] In some embodiments, the pore-forming agent is hydrogen peroxide, or a combination of sodium hypochlorite and hydrogen peroxide, or a combination of hydrogen peroxide and a ferrous salt, or a combination of hydrogen peroxide and ammonia, or a combination of hydrogen peroxide and an organic base. Preferably, the pore-forming agent is a combination of sodium hypochlorite and hydrogen peroxide, or a combination of hydrogen peroxide and a ferrous salt, or a combination of hydrogen peroxide and ammonia, or a combination of hydrogen peroxide and an organic base.

[0027] In some embodiments, when the pore-forming agent is hydrogen peroxide, the porous graphene oxide is prepared by forming pores in graphene oxide using the pore-forming agent. This includes reacting a mixed solution of graphene oxide and hydrogen peroxide at 45-60°C for 6-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, to obtain the porous graphene oxide. Preferably, the mass ratio of hydrogen peroxide to graphene oxide is (3-20):1. Preferably, the content of graphene oxide in the mixed solution of graphene oxide and hydrogen peroxide is 0.25-10 mg / mL, more preferably 1-4 mg / mL. When hydrogen peroxide is used alone to etch graphene oxide for pore formation, because hydrogen peroxide has a relatively mild oxidizing property, it can usually only etch existing defects on the graphene oxide sheets to form pores, and it is difficult to etch more defects by its own oxidizing property, thus the pore-forming effect is limited. Meanwhile, this reaction generally needs to be carried out at a relatively high temperature (the reaction is extremely slow at around 25°C at room temperature), but excessively high temperatures may cause graphene oxide to be reduced and its dispersibility to deteriorate. Therefore, using hydrogen peroxide alone as a pore-forming agent is not a preferred solution of this invention.

[0028] In some embodiments, when the pore-forming agent is a combination of sodium hypochlorite and hydrogen peroxide, the porous graphene oxide is prepared by creating pores in the graphene oxide using the pore-forming agent. This process includes: first, reacting a mixed solution of graphene oxide and sodium hypochlorite at 5-25°C for 12-30 hours, with the mass ratio of sodium hypochlorite to graphene oxide being 1:100-1:10, to obtain pretreated graphene oxide; then, reacting the mixed solution of the pretreated graphene oxide and hydrogen peroxide at 45-60°C for 12-48 hours, with the mass ratio of hydrogen peroxide to the pretreated graphene oxide being (1-100):1, to obtain the porous graphene oxide. Preferably, the mass ratio of hydrogen peroxide to the pretreated graphene oxide is (3-20):1. Preferably, the graphene oxide content in the mixed solution of graphene oxide and sodium hypochlorite is 0.25-10 mg / mL, more preferably 1-4 mg / mL. Hydrogen peroxide's oxidizing properties are not particularly strong; it can typically only etch existing defects into pores on graphene oxide sheets, and it is difficult to etch out more defects using its own oxidizing properties. This invention preferably uses a small amount of sodium hypochlorite, which has stronger oxidizing properties, to etch out more defects on the graphene oxide sheets at a lower temperature beforehand, and then uses mild hydrogen peroxide to etch out more pores, thereby increasing the pore density and etching efficiency.

[0029] In some embodiments, when the pore-forming agent is a combination of hydrogen peroxide and ferrous salt, the porous graphene oxide is prepared by creating pores in the graphene oxide using the pore-forming agent. This includes reacting a mixed solution of graphene oxide, hydrogen peroxide, and ferrous salt at 25-45°C for 12-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the mass ratio of ferrous salt to graphene oxide is 1:100-1:10, thereby obtaining the porous graphene oxide. Preferably, the mass ratio of hydrogen peroxide to graphene oxide is (3-20):1. Preferably, the graphene oxide content in the mixed solution of graphene oxide, hydrogen peroxide, and ferrous salt is 0.25-10 mg / mL, more preferably 1-4 mg / mL. The present invention preferably uses Fe... 2+ When used in conjunction with hydrogen peroxide, the Fenton reaction generates more potent hydroxyl radicals (·OH), which can etch more pores at lower temperatures, significantly improving pore-forming efficiency. Furthermore, the Fe generated by the Fenton reaction... 3+ Hydrolysis forms iron colloids (such as Fe(OH)3). These iron colloids interact with the graphene oxide sheets, increasing the effective particle size of the graphene oxide. This makes the graphene oxide easier to separate by centrifugal sedimentation, facilitating subsequent removal of residual H2O2 and Fe by centrifugal washing. 2+ and newly generated Fe 3+ .

[0030] In some embodiments, when the pore-forming agent is a combination of hydrogen peroxide and ammonia, the porous graphene oxide is prepared by forming pores in the graphene oxide using the pore-forming agent. This includes reacting a mixed solution of graphene oxide, hydrogen peroxide, and ammonia at 25-45°C for 12-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the ammonia is used to adjust the pH of the mixed solution to 9-12.5, thereby obtaining the porous graphene oxide. Preferably, the mass ratio of hydrogen peroxide to graphene oxide is (3-20):1. Preferably, the graphene oxide content in the mixed solution of graphene oxide, hydrogen peroxide, and ammonia is 0.25-10 mg / mL, more preferably 1-4 mg / mL. The present invention preferably uses a combination of hydrogen peroxide and ammonia. Under alkaline conditions (the pH is adjusted to 9-12.5 by ammonia), hydrogen peroxide undergoes alkaline catalytic decomposition, which generates reactive oxygen species with stronger oxidizing power. These reactive oxygen species have a significantly stronger oxidizing ability than hydrogen peroxide itself, and can etch more pores at lower temperatures, thereby improving pore-forming efficiency.

[0031] In some embodiments, when the pore-forming agent is a combination of hydrogen peroxide and an organic base, the porous graphene oxide is prepared by forming pores in the graphene oxide using the pore-forming agent. This includes reacting a mixed solution of graphene oxide, hydrogen peroxide, and an organic base at 25-60°C for 2-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the mass ratio of the organic base to hydrogen peroxide is 1:2-1:20, thereby obtaining the porous graphene oxide. Preferably, the mass ratio of hydrogen peroxide to graphene oxide is (3-20):1. Preferably, the mass ratio of the organic base to hydrogen peroxide is 1:5-1:10. Preferably, the organic base includes a C6-C12 tertiary amine compound. More preferably, the organic base includes one or more of triethylamine, tripropylamine, and tributylamine. Preferably, the graphene oxide content in the mixed solution of graphene oxide, hydrogen peroxide, and organic base is 0.25-10 mg / mL, more preferably 1-4 mg / mL. This invention preferably uses a combination of hydrogen peroxide and an organic base, where the organic base promotes the alkaline-catalyzed decomposition of hydrogen peroxide to generate hydrogen peroxide anions (HO2). - More reactive oxygen species, such as hydroxyl radicals (·OH), can be used to etch more pores at lower temperatures, improving pore-forming efficiency. Meanwhile, compared to ammonia, organic bases have higher boiling points and are less prone to volatilization during the reaction, maintaining a more stable alkaline environment. Further optimized C6-C12 tertiary amine compounds lack NH bonds, are less susceptible to consumption by hydrogen peroxide, and are more stable in the reaction system.

[0032] Existing technologies include methods for preparing porous graphene oxide by etching graphene oxide with alkaline solutions or oxidizing agents. However, alkaline heat treatment, while etching nanopores, can also reduce graphene oxide, leading to decreased dispersibility and even solution aggregation. In contrast, this invention uses hydrogen peroxide as the primary pore-forming agent, which etches nanopores without reducing the dispersibility of graphene oxide. After etching, residual hydrogen peroxide can be removed by multiple rounds of centrifugation. However, it should be noted that the etching process reduces the size of graphene oxide sheets, making centrifugal separation difficult. Furthermore, since the reaction rate between hydrogen peroxide and graphene oxide is slow at room temperature or low temperatures, when using an oxidation-resistant crosslinking agent, residual hydrogen peroxide can be left unremoved after etching, and subsequent crosslinking steps can be performed directly, thus simplifying the process. Alternatively, manganese dioxide can be added to catalyze the decomposition of hydrogen peroxide, followed by low-speed centrifugation (500-2000 rpm) to obtain porous graphene oxide from the supernatant. Alternatively, porous graphene oxide can be centrifuged at high speed (10,000-15,000 rpm) and hydrogen peroxide can be removed by multiple rounds of centrifugation-washing dispersion.

[0033] This invention uses hydrogen peroxide as the primary pore-forming agent, and preferably supplements it with the aforementioned NaClO, ammonia, and Fe. 2+ Chemical etching of graphene oxide using additives such as organic bases can enhance pore-forming effects and create nanoscale pores. Among these, the combination of hydrogen peroxide and C6-C12 tertiary amine compounds is the most preferred pore-forming agent combination. Compared to NaClO, tertiary amine compounds regulate the decomposition rate of hydrogen peroxide through a base catalytic mechanism, resulting in a gentler etching process that is beneficial for forming nanopores with uniform pore size. NaClO, on the other hand, has strong oxidizing properties, which may lead to over-oxidation of graphene oxide sheets or even structural damage; the combination of Fe... 2+ In comparison, tertiary amine compounds do not contain metal ions, resulting in a cleaner reaction system that eliminates the need for subsequent iron removal steps and avoids the uncontrollable pore size problem caused by the excessively rapid generation rate of hydroxyl radicals in the Fenton reaction. Compared to ammonia, tertiary amine compounds have higher boiling points and are less volatile. They also do not contain NH bonds and are not consumed by hydrogen peroxide, thus maintaining a more stable alkaline environment throughout the reaction process. This leads to the production of porous graphene oxide with a more uniform pore size distribution and higher pore density.

[0034] In some embodiments, the porous graphene oxide exhibits a bimodal pore size distribution, comprising micropores and macropores. The average pore size of the micropores is 0.5-2 nm, and the average pore size of the macropores is 2-50 nm (preferably 10-50 nm). The micropores account for more than 75% of the total number of pores (preferably more than 80%, more preferably more than 85%, and even more preferably more than 90%). The micropores are nanofiltration functional pores, allowing water molecules and inorganic salt ions to pass through while retaining dye molecules. The macropores are mainly defects at the edges of graphene oxide sheets or interlayer pores. The porous graphene oxide of the present invention, dominated by micropores, exhibits high salt / dye separation performance.

[0035] In some embodiments, the crosslinking agent includes an ionic crosslinking agent and / or a chemical crosslinking agent. Preferably, the ionic crosslinking agent includes Ca... 2+ Mg 2+ and Fe 3+ One or more of the following. More preferably, the ionic crosslinking agent is Fe. 3+Preferably, the chemical crosslinking agent includes one or more of carboxyl crosslinking agents, hydroxyl crosslinking agents, and multifunctional crosslinking agents. More preferably, the carboxyl crosslinking agent includes one or more of polyamines, multifunctional aziridines, and polycarbodiimides; the hydroxyl crosslinking agent includes one or more of polyaldehydes, isocyanates, and borax; and the multifunctional crosslinking agent includes polyphenols and / or siloxanes. Specifically, the chemical crosslinking agent includes one or more of tannic acid, glutaraldehyde, borax, polyethyleneimine, 3-aminopropyltriethoxysilane, and (3-glycidylpropoxy)trimethoxysilane. It is understood that the carboxyl crosslinking agent refers to a crosslinking agent that mainly reacts with carboxyl groups (-COOH), the hydroxyl crosslinking agent refers to a crosslinking agent that mainly reacts with hydroxyl groups (-OH), and the multifunctional crosslinking agent refers to a crosslinking agent that contains two or more functional groups that can participate in the crosslinking reaction and can achieve crosslinking through covalent bonds and / or non-covalent bond interactions (such as hydrogen bonds, hydrophobic interactions, coordination bonds, etc.).

[0036] In some embodiments, the crosslinking agent accounts for 1-50% of the mass of the porous graphene oxide, preferably 3-30%.

[0037] In some embodiments, the porous graphene oxide membrane further contains polymeric nanomaterials. Preferably, the polymeric nanomaterials include one or more of the following: cellulose nanofibers, cellulose nanocrystals, chitin nanofibers, chitin nanocrystals, chitosan nanofibers, chitosan nanocrystals, lignin nanofibers, and lignin nanocrystals. Preferably, the mass ratio of the polymeric nanomaterials to the porous graphene oxide is (0.5-5):1.

[0038] In some embodiments, the thickness of the porous graphene oxide film is 10-500 nm, preferably 20-100 nm.

[0039] In some embodiments, the base membrane is an ultrafiltration membrane or a microfiltration membrane. Preferably, the average pore size of the base membrane is 0.01-5 μm, more preferably 0.05-0.5 μm.

[0040] In some embodiments, the base film is made of one or more of the following materials: nylon (such as PA6 or PA66), polyethersulfone (PES), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), cellulose acetate (CA), and polypropylene (PP). Preferably, the base film is made of one or more of the following materials: nylon 6, polyethersulfone, and polyvinylidene fluoride.

[0041] In some embodiments, the thickness of the base film is 50-200 μm.

[0042] In some embodiments, the porous graphene oxide composite nanofiltration membrane has a molecular weight cutoff of 1000-5000 Daltons, a rejection rate of ≥95% for reactive dyes, and a rejection rate of <12% for inorganic salts (i.e., desalination rate).

[0043] According to a specific embodiment of the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned porous graphene oxide composite nanofiltration membrane, which includes the following steps: A mixture containing porous graphene oxide and a crosslinking agent is coated onto the surface of a base membrane to carry out a crosslinking reaction, forming a porous graphene oxide membrane, thus obtaining the porous graphene oxide composite nanofiltration membrane.

[0044] In some embodiments, the mixture containing porous graphene oxide and a crosslinking agent further contains polymeric nanomaterials.

[0045] In some embodiments, the content of porous graphene oxide in the mixture containing porous graphene oxide and crosslinking agent is 1-10 mg / mL, preferably 2-5 mg / mL.

[0046] In some embodiments, in the mixture containing porous graphene oxide and a crosslinking agent, the crosslinking agent accounts for 1-50% of the mass of the porous graphene oxide, preferably 3-30%.

[0047] In some embodiments, the coating method includes one or more of blade coating, wire bar coating, slot coating, and microgravure coating.

[0048] In some embodiments, a mixture containing porous graphene oxide and a crosslinking agent is coated onto the surface of a base film to form a wet film, the thickness of which is 5-100 μm, preferably 10-25 μm.

[0049] In some embodiments, the crosslinking reaction is carried out at a temperature of 20-100°C for a time of 5 minutes to 48 hours.

[0050] The porous graphene oxide composite nanofiltration membrane of the present invention has a simple preparation process and is easy to mass-produce. Furthermore, the porous graphene oxide composite nanofiltration membrane of the present invention has a stable structure, good bonding force between the porous graphene oxide membrane and the base membrane, stable performance, and excellent inorganic salt / dye separation performance. It can be applied to the treatment of high-salt wastewater containing dyes, desalination and purification of salt-containing dyes, and purification of municipal water.

[0051] According to a specific embodiment of the third aspect of the present invention, the present invention provides the application of the above-mentioned porous graphene oxide composite nanofiltration membrane in the treatment of high-salt wastewater containing dyes and / or the desalination and purification of salt-containing dyes.

[0052] In some embodiments, the salt concentration in the dye-containing high-salt wastewater is above 20 g / L, and the dye concentration is 0.1-5 g / L. Preferably, the salt includes one or more of NaCl, Na2SO4, and Na2CO3.

[0053] In some embodiments, the flux of the porous graphene oxide composite nanofiltration membrane for treating the dye-containing high-salt wastewater is 5-20 L / (m²). 2 (·h·Bar), dye retention rate is 95%-99.9%, desalination rate is <12%.

[0054] The technical solutions of the present invention are specifically illustrated below through embodiments, but the present invention is not limited to these embodiments. Of course, various modifications can be made within the scope of the key points of the present invention.

[0055] Test method: Pore ​​size characterization of porous graphene oxide: The pore size distribution of porous graphene oxide was determined by nitrogen adsorption-desorption (BET). The pore morphology on the surface of porous graphene oxide sheets was observed by atomic force microscopy (AFM). The pore size of each pore in the AFM images was measured and counted to obtain the pore size distribution in terms of the number of pores. Based on this, the proportion of small pores (0.5-2 nm) to the total number of pores was calculated.

[0056] Molecular weight cutoff (MWCO) test: A 1 g / L solution of polyethylene glycol (PEG) standard with different molecular weights was prepared as the feed solution, and the cutoff rate was tested at 25℃ and 1 Bar. The PEG molecular weight corresponding to a cutoff rate of 90% is the molecular weight cutoff of the membrane.

[0057] Preparation Example 1

[0058] A mixed aqueous solution containing 2.5 mg / mL GO (with sheet size of 3-10 μm; the same GO was used in the following preparation examples) and 50 mg / mL H2O2 was prepared and reacted with continuous stirring at 60 °C for 6 h to obtain porous graphene oxide. After the reaction, residual H2O2 was removed by centrifugation and washing 3-4 times, and the solution was refrigerated for later use.

[0059] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 1.3 nm, and the average pore size of the macropores is 45 nm. In terms of the number of pores, the micropores account for 78% of the total number of pores.

[0060] Preparation Example 2

[0061] A mixed aqueous solution containing 4 mg / mL GO and 0.25 mg / mL NaClO was prepared and reacted with continuous stirring at room temperature for 24 h to obtain porous graphene oxide. Subsequently, H2O2 (12.5 mg / mL) was added to the solution, and the reaction was carried out at 60℃ for 30 h to prepare porous graphene oxide. After the reaction, residual NaClO and H2O2 were removed by 3-4 rounds of centrifugation washing, and the solution was sealed and stored at room temperature for later use.

[0062] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 1.4 nm, and the average pore size of the macropores is 40 nm. In terms of the number of pores, the micropores account for 88% of the total number of pores.

[0063] Preparation Example 3

[0064] A 3 mg / mL GO aqueous solution was prepared, followed by the addition of H2O2 (30 mg / mL) and FeSO4 (0.08 mg / mL). The mixture was stirred continuously at 45 °C for 15 h to obtain porous graphene oxide. After the reaction, residual H2O2 and iron ions were removed by centrifugation and washing 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0065] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 1.5 nm, and the average pore size of the macropores is 35 nm. In terms of the number of pores, the micropores account for 92% of the total number of pores.

[0066] Preparation Example 4

[0067] A 4 mg / mL GO aqueous solution was prepared, followed by the addition of 20 mg / mL H2O2 and the adjustment of the pH to 12 with ammonia. The reaction was carried out with continuous stirring at 40 °C for 30 h to obtain porous graphene oxide. After the reaction, residual H2O2 was removed by centrifugation and washing 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0068] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 1.4 nm, and the average pore size of the macropores is 38 nm. In terms of the number of pores, the micropores account for 90% of the total number of pores.

[0069] Preparation Example 5

[0070] A 4 mg / mL GO aqueous solution was prepared, followed by the addition of H2O2 (20 mg / mL) and triethylamine (2 mg / mL). The mixture was stirred continuously at 50 °C for 4 h to obtain porous graphene oxide. After the reaction, residual H2O2 and triethylamine were removed by centrifugation and washing 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0071] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 1.6 nm, and the average pore size of the macropores is 32 nm. In terms of the number of pores, the micropores account for 94% of the total number of pores.

[0072] Comparative Preparation Example 1

[0073] A 4 mg / mL GO aqueous solution was prepared, and then concentrated sulfuric acid (50 mg / mL based on pure substance) was added to it. After stirring continuously at room temperature for 2 h, porous graphene oxide was obtained. After the reaction, residual concentrated sulfuric acid was removed by centrifugation 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0074] The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 2.5 nm, and the average pore size of the macropores is 30 nm. In terms of the number of pores, the micropores account for 45% of the total number of pores.

[0075] Comparative Preparation Example 2

[0076] A 4 mg / mL GO aqueous solution was prepared, and then NaOH (20 mg / mL) was added to it. After stirring continuously at 80 °C for 4 h, porous graphene oxide was obtained. After the reaction, residual NaOH was removed by centrifugation and washing 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0077] The porous graphene oxide has a wide pore size distribution and does not exhibit a typical bimodal distribution, with an average pore size of 4.8 nm. In terms of the number of pores, pores with a diameter in the range of 0.5-2 nm account for 35% of the total number of pores.

[0078] Comparative preparation example 3

[0079] A 4 mg / mL GO aqueous solution was prepared, and then potassium permanganate (5 mg / mL) was added. After stirring continuously at room temperature for 6 h, porous graphene oxide was obtained. After the reaction, residual potassium permanganate and the generated manganese compounds were removed by centrifugation and washing 3-4 times, and the solution was sealed and stored at room temperature for later use.

[0080] The porous graphene oxide has a wide pore size distribution and does not exhibit a typical bimodal distribution, with an average pore size of 3.2 nm. In terms of the number of pores, pores with a diameter in the range of 0.5-2 nm account for 40% of the total number of pores.

[0081] Example 1

[0082] Take 100 mL of the 2.5 mg / mL porous graphene oxide solution prepared in Preparation Example 1, and adjust its pH to 10.5 using sodium hydroxide. Then, add 5 mL of 1% PEI-600 solution, followed by adding deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir at room temperature for 30 minutes to ensure uniform dispersion of the porous graphene oxide and PEI-600, obtaining a mixed solution. Subsequently, use a coating machine to uniformly coat the mixed solution onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 25 μm. Then, react at 90℃ for 15 minutes to form a porous graphene oxide membrane (thickness 80 nm), obtaining a porous graphene oxide composite nanofiltration membrane.

[0083] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1200 Daltons.

[0084] Example 2

[0085] Take 100 mL of the 4 mg / mL porous graphene oxide solution prepared according to Preparation Example 1, and adjust its pH to 10.5 using ammonia. Then, add 20 mg of aziridine crosslinking agent (CX-100), followed by adding deionized water to dilute the porous graphene oxide concentration to 3 mg / mL. Stir at room temperature for 30 minutes to uniformly disperse the porous graphene oxide and aziridine crosslinking agent, obtaining a mixture. Subsequently, use a coating machine to uniformly coat the mixture onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 15 μm. Then, react at 70°C for 15 minutes to form a porous graphene oxide membrane (thickness 89 nm), obtaining a porous graphene oxide composite nanofiltration membrane.

[0086] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1080 Daltons.

[0087] Example 3

[0088] Take 100 mL of a 5 mg / mL porous graphene oxide solution prepared according to Preparation Example 1, and adjust its pH to 10.5 using ammonia. Then, add 100 mL of a 1% (w / w) cellulose nanofiber solution and 25 mg of aziridine crosslinking agent (CX-100). Subsequently, add deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir at room temperature for 30 minutes to uniformly disperse the porous graphene oxide, cellulose nanofibers, and aziridine crosslinking agent, obtaining a mixed solution. Then, use a coating machine to uniformly coat the mixed solution onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 20 μm. Then, react at 70°C for 15 minutes to form a porous graphene oxide membrane (thickness 92 nm), obtaining a porous graphene oxide composite nanofiltration membrane.

[0089] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1090 Daltons.

[0090] Example 4

[0091] Take 100 mL of a 3 mg / mL porous graphene oxide solution prepared according to Preparation Example 1, and adjust its pH to 3.5 with hydrochloric acid. Then add 60 μL of a 50% glutaraldehyde solution (graphene oxide:glutaraldehyde = 10:1). Subsequently, add deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir overnight at room temperature to allow the porous graphene oxide and glutaraldehyde to disperse evenly and undergo pre-crosslinking, resulting in a mixed solution. Then, use a coating machine to uniformly coat the mixed solution onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 25 μm. Then react at 70°C for 15 minutes to form a porous graphene oxide membrane (thickness 86 nm), thus obtaining a porous graphene oxide composite nanofiltration membrane.

[0092] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1120 Daltons.

[0093] Example 5

[0094] Take 100 mL of a 3 mg / mL porous graphene oxide solution prepared according to Preparation Example 1, and adjust its pH to 3.5 with acetic acid. Then add 100 mL of a 1% (w / w) cellulose nanofiber solution and 60 μL of a 50% (w / w) glutaraldehyde solution (graphene oxide:glutaraldehyde = 10:1). Subsequently, add deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir overnight at room temperature to allow the porous graphene oxide, cellulose nanofibers, and glutaraldehyde to disperse evenly and undergo pre-crosslinking, resulting in a mixed solution. Then, use a coating machine to uniformly coat the mixed solution onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 25 μm. Then react at 70°C for 15 minutes to form a porous graphene oxide membrane (thickness 90 nm), thus obtaining a porous graphene oxide composite nanofiltration membrane.

[0095] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1000 Daltons.

[0096] Example 6

[0097] 100 mL of the 2.5 mg / mL porous graphene oxide solution prepared in Preparation Example 1 was taken, and 0.15 mL of a 20 mg / mL tannic acid (TA) aqueous solution and 0.15 mL of a 20 mg / mL 3-aminopropyltriethoxysilane (APTES) ethanol solution were added sequentially. Deionized water was then added to dilute the porous graphene oxide concentration to 2 mg / mL, and the pH was adjusted to 10 using triethylamine. The mixture was stirred at room temperature for 30 h to allow the porous graphene oxide, TA, and APTES to be uniformly dispersed and pre-crosslinked, resulting in a mixed solution. Subsequently, using a coating machine, the mixed solution was uniformly coated onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 25 μm. The membrane was then reacted at 70 °C for 15 minutes to form a porous graphene oxide membrane (thickness 100 nm), thus obtaining a porous graphene oxide composite nanofiltration membrane.

[0098] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1100 Daltons.

[0099] Example 7

[0100] Take 100 mL of the 2.5 mg / mL porous graphene oxide solution prepared in Preparation Example 1, and adjust its pH to 10.5 using sodium hydroxide. Then, add 5 mL of a 1% (3-glycidylpropoxy)trimethoxysilane (GLMYO) solution, followed by adding deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir at room temperature for 30 minutes to ensure uniform dispersion of the porous graphene oxide and GLMYO, obtaining a mixed solution. Subsequently, use a coating machine to uniformly coat the mixed solution onto a nylon-based membrane (average pore size 0.10 μm, thickness 50-200 μm) to form a wet membrane with a thickness of 25 μm. Then, react at 90℃ for 30 minutes to form a porous graphene oxide membrane (thickness 95 nm), obtaining a porous graphene oxide composite nanofiltration membrane.

[0101] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1250 Daltons.

[0102] Example 8

[0103] Take 100 mL of the 4 mg / mL porous graphene oxide solution prepared according to Preparation Example 1, add 20 mg of isocyanate crosslinking agent (IPDI), and then add deionized water to dilute the porous graphene oxide concentration to 2 mg / mL. Stir at room temperature for 30 minutes to uniformly disperse the porous graphene oxide and isocyanate crosslinking agent, obtaining a mixture. Then, use a coating machine to uniformly coat the mixture onto a nylon-based membrane (average pore size of 0.10 μm, thickness of 50-200 μm) to form a wet membrane with a thickness of 20 μm. Then, react at 70°C for 15 minutes to form a porous graphene oxide membrane (thickness of 86 nm), obtaining a porous graphene oxide composite nanofiltration membrane.

[0104] The porous graphene oxide composite nanofiltration membrane in this embodiment has a molecular weight cutoff of 1180 Daltons.

[0105] Example 9

[0106] This embodiment is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Preparation Example 2, and the rest is the same as Example 8.

[0107] The porous graphene oxide composite nanofiltration membrane in this embodiment has a thickness of 90 nm and a molecular weight cutoff of 1280 Daltons.

[0108] Example 10

[0109] This embodiment is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Preparation Example 3, and the rest is the same as Example 8.

[0110] The porous graphene oxide composite nanofiltration membrane in this embodiment has a thickness of 85 nm and a molecular weight cutoff of 1470 Daltons.

[0111] Example 11

[0112] This embodiment is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Preparation Example 4, and the rest is the same as Example 8.

[0113] The porous graphene oxide composite nanofiltration membrane in this embodiment has a thickness of 75 nm and a molecular weight cutoff of 1560 Daltons.

[0114] Example 12

[0115] This embodiment is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Preparation Example 5, and the rest is the same as Example 8.

[0116] The porous graphene oxide composite nanofiltration membrane in this embodiment has a thickness of 70 nm and a molecular weight cutoff of 1600 Daltons.

[0117] Comparative Example 1

[0118] This comparative example is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Comparative Preparation Example 1, and the rest is the same as Example 8.

[0119] The porous graphene oxide composite nanofiltration membrane in this comparative example has a thickness of 110 nm and a molecular weight cutoff of 1050 Daltons.

[0120] Comparative Example 2

[0121] This comparative example is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Comparative Preparation Example 2, and the rest is the same as Example 8.

[0122] The porous graphene oxide composite nanofiltration membrane in this comparative example has a thickness of 100 nm and a molecular weight cutoff of 1020 Daltons.

[0123] Comparative Example 3

[0124] This comparative example is basically the same as Example 8, except that the porous graphene oxide solution was prepared in Comparative Preparation Example 3, and the rest is the same as Example 8.

[0125] The porous graphene oxide composite nanofiltration membrane in this comparative example has a thickness of 105 nm and a molecular weight cutoff of 1000 Daltons.

[0126] Comparative Example 4

[0127] This comparative example is basically the same as Example 8, except that a graphene oxide solution (in which the GO is the same as in Preparation Example 1) is used instead of a porous graphene oxide solution. All other aspects are the same as in Example 8.

[0128] The graphene oxide membrane in this comparative example has a thickness of 160 nm and a molecular weight cutoff of 980 Daltons.

[0129] Test case

[0130] (1) Flux test: The composite nanofiltration membrane is loaded into a dead-end filter or a cross-flow filter. At 25°C and 4 Bar pressure, a mixed solution of 70 g / L Na2SO4 and 2 g / L reactive dye (such as BlueR) is used as the feed liquid. After pre-pressurization for 30 minutes, the permeate is collected, and the flux is calculated according to the following formula: J = V / (A×t×P), where J is the flux (L / (m 2 ·h·Bar), V is the permeate volume (L), A is the effective membrane area (m²), t is the test time (h), and P is the operating pressure (Bar).

[0131] (2) Dye Retention Rate Test: The absorbance of the dye in the feed solution and the permeate was measured using a UV-Vis spectrophotometer (at the maximum absorption wavelength of the dye). The dye retention rate was calculated using the following formula: R = (1 - Cp / Cf) × 100%, where R is the retention rate (%), Cp is the dye concentration in the permeate, and Cf is the dye concentration in the feed solution.

[0132] (3) Desalination rate test: The conductivity of the feed liquid and the permeate is measured by a conductivity meter, and the desalination rate is calculated according to the following formula: Rs = (1 - κp / κf) × 100%, where Rs is the desalination rate (%), κp is the conductivity of the permeate, and κf is the conductivity of the feed liquid.

[0133] Porous graphene oxide was prepared according to the method of Preparation Example 1, but the reaction temperature and time were adjusted. Then, a porous graphene oxide composite nanofiltration membrane was prepared according to the method of Example 1. The flux and dye rejection rate of the composite nanofiltration membranes formed by the porous graphene oxide prepared under different etching temperatures and times are shown in Table 1.

[0134] Table 1

[0135] As shown in Table 1, with increasing etching temperature and etching time, the flux of the composite nanofiltration membrane gradually increases, while the dye rejection initially increases slightly and then gradually decreases. This indicates that hydrogen peroxide can etch nanopores into the graphene oxide surface, significantly improving the flux of the GO membrane. However, excessive etching leads to a significant decrease in dye rejection. Specifically, the etching reaction rate is slow at 25℃, resulting in limited flux improvement (5-8 L / (m²)). 2 While the dye rejection rate remained above 94%, the flux increased significantly over time at 45°C (5-15 L / (m²)). 2 The flux was measured at ·h·Bar), and the dye rejection rate remained above 92% within the range of 6-20 h, achieving a good balance between flux and rejection rate; at 60℃, the flux was significantly increased (reaching a maximum of 23.5 L / (m²). 2 While the etching rate is relatively fast (·h·Bar), the dye retention rate drops sharply after 6 hours (82.3% at 12 hours and only 32.3% at 30 hours). Considering both throughput and dye retention rate, the preferred etching temperature is 45-60℃ and the etching time is 6-20 hours; a more preferred etching temperature is 45℃ and the etching time is 6-20 hours.

[0136] Porous graphene oxide composite nanofiltration membranes were prepared according to the method in Example 8, but the content of isocyanate crosslinking agent and the porous graphene oxide solution were adjusted to obtain different composite nanofiltration membranes. Their flux and dye rejection rates are shown in Table 2.

[0137] Table 2

[0138] Table 2 shows that, under the same crosslinking agent content, the crosslinked composite membrane formed by porous graphene oxide etched with hydrogen peroxide exhibits significantly higher flux than the unetched graphene oxide composite nanofiltration membrane. Under conditions of comparable dye rejection rates (both above 97%), the flux of the porous graphene oxide composite nanofiltration membrane can reach 2-6 times that of the un-pored membrane, indicating that the nanopores formed on the graphene oxide sheets by hydrogen peroxide etching effectively enhance the intrinsic flux of the membrane. More importantly, for the un-pored graphene oxide membrane, when the crosslinking agent content increases to 0.3 mg / mL and 1 mg / mL, the flux drops sharply to 1.02 and 0.30 L / (m²), respectively. 2 The flux of graphene oxide membranes with a crosslinking agent content of 0.3 mg / mL (·h·Bar) is almost negligible, rendering them practically useless; however, for porous graphene oxide membranes with pores, they still maintain a high flux at the same crosslinking agent content (e.g., 6.7 L / (m²) in Preparation Example 1 at 0.3 mg / mL). 2 ·h·Bar), at 1 mg / mL, it is 2.8 L / (m2 This indicates that, due to the significant increase in intrinsic flux of porous graphene oxide after pore formation, the membrane can maintain a high flux even with higher crosslinking agent dosages. Therefore, this invention can achieve a higher degree of crosslinking than unpore-formed graphene oxide. The higher degree of crosslinking not only further improves the dye rejection rate of the membrane but also enhances the interlayer bonding force of graphene oxide and the interfacial bonding force between the graphene oxide membrane and the base membrane, thereby improving the overall stability of the composite nanofiltration membrane.

[0139] The throughput, dye rejection rate, and desalination rate of the above embodiments and comparative examples are shown in Table 3.

[0140] Table 3

[0141] As shown in Table 3, the composite nanofiltration membranes formed from porous graphene oxide prepared in Examples 2-5 using additives exhibit superior flux and separation performance compared to the composite nanofiltration membrane formed from porous graphene oxide prepared in Example 1 without additives. In particular, Example 5, which used a tertiary amine as an additive, demonstrated even better results.

[0142] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A porous graphene oxide composite nanofiltration membrane, comprising: A base film, and a porous graphene oxide film formed on the surface of the base film; The porous graphene oxide membrane contains porous graphene oxide, and the porous graphene oxide membrane is formed on the surface of the base membrane by crosslinking through a crosslinking agent; the porous graphene oxide is obtained by creating pores in the graphene oxide using a pore-forming agent, the pore-forming agent including a main pore-forming agent and selectively including an auxiliary agent, wherein the main pore-forming agent is hydrogen peroxide.

2. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, In the pore-forming agent, the auxiliary agent includes one or more of strong oxidizing agents, inorganic bases, organic bases, and ferrous salts.

3. The porous graphene oxide composite nanofiltration membrane according to claim 2, wherein, The strong oxidant includes one or more of sodium hypochlorite, ozone, and potassium permanganate. And / or, the inorganic base includes NaOH and / or ammonia; And / or, the organic base includes C6-C12 tertiary amine compounds; And / or, the organic base includes one or more of triethylamine, tripropylamine and tributylamine; And / or, the ferrous salt includes ferrous sulfate and / or ferrous chloride.

4. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, In the process of preparing porous graphene oxide by creating pores in graphene oxide with a pore-forming agent, the mass ratio of hydrogen peroxide to graphene oxide is (1-100):

1. And / or, the sheet size of the graphene oxide is 0.5-100 μm.

5. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The pore-forming agent is hydrogen peroxide, or a combination of sodium hypochlorite and hydrogen peroxide, or a combination of hydrogen peroxide and ferrous salt, or a combination of hydrogen peroxide and ammonia, or a combination of hydrogen peroxide and organic base.

6. The porous graphene oxide composite nanofiltration membrane according to claim 5, wherein, When the pore-forming agent is hydrogen peroxide, the porous graphene oxide is prepared by forming pores in graphene oxide using the pore-forming agent. This includes reacting a mixed solution of graphene oxide and hydrogen peroxide at 45-60°C for 6-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, thereby obtaining the porous graphene oxide. And / or, when the pore-forming agent is a combination of sodium hypochlorite and hydrogen peroxide, the porous graphene oxide is prepared by forming pores in the graphene oxide using the pore-forming agent, comprising: first reacting a mixed solution of graphene oxide and sodium hypochlorite at 5-25°C for 12-30 hours, wherein the mass ratio of sodium hypochlorite to graphene oxide is 1:100-1:10, to obtain pretreated graphene oxide; then reacting a mixed solution of the pretreated graphene oxide and hydrogen peroxide at 45-60°C for 12-48 hours, wherein the mass ratio of hydrogen peroxide to the pretreated graphene oxide is (1-100):1, to obtain the porous graphene oxide. And / or, when the pore-forming agent is a combination of hydrogen peroxide and ferrous salt, the porous graphene oxide is prepared by forming pores in graphene oxide using the pore-forming agent, which includes: reacting a mixed solution of graphene oxide, hydrogen peroxide and ferrous salt at 25-45°C for 12-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the mass ratio of ferrous salt to graphene oxide is 1:100-1:10, thereby obtaining the porous graphene oxide. And / or, when the pore-forming agent is a combination of hydrogen peroxide and ammonia, the porous graphene oxide is prepared by forming pores in the graphene oxide using the pore-forming agent, comprising: reacting a mixed solution of graphene oxide, hydrogen peroxide, and ammonia at 25-45°C for 12-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the ammonia is used to adjust the pH of the mixed solution of graphene oxide, hydrogen peroxide, and ammonia to 9-12.5, thereby obtaining the porous graphene oxide; And / or, when the pore-forming agent is a combination of hydrogen peroxide and an organic base, the porous graphene oxide is prepared by forming pores in the graphene oxide using the pore-forming agent, which includes: reacting a mixed solution of graphene oxide, hydrogen peroxide, and an organic base at 25-60°C for 2-48 hours, wherein the mass ratio of hydrogen peroxide to graphene oxide is (1-100):1, and the mass ratio of the organic base to hydrogen peroxide is 1:2-1:20, thereby obtaining the porous graphene oxide.

7. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The porous graphene oxide has a bimodal pore size distribution, including micropores and macropores. The average pore size of the micropores is 0.5-2 nm, and the average pore size of the macropores is 2-50 nm. In terms of the number of pores, the micropores account for more than 75% of the total number of pores.

8. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The crosslinking agent includes ionic crosslinking agents and / or chemical crosslinking agents; And / or, the crosslinking agent accounts for 1-50% of the mass of the porous graphene oxide.

9. The porous graphene oxide composite nanofiltration membrane according to claim 8, wherein, The ionic crosslinking agent includes Ca. 2+ Mg 2+ and Fe 3+ One or more of the following; And / or, the chemical crosslinking agent includes one or more of carboxyl crosslinking agents, hydroxyl crosslinking agents, and multifunctional crosslinking agents.

10. The porous graphene oxide composite nanofiltration membrane according to claim 9, wherein, The carboxyl crosslinking agent includes one or more of the following: polyamines, polyfunctional aziridines, and polycarbodiimides. And / or, the hydroxyl crosslinking agent includes one or more of polyaldehydes, isocyanates and borax; And / or, the multifunctional crosslinking agent includes polyphenols and / or siloxanes; And / or, the chemical crosslinking agent includes one or more of tannic acid, glutaraldehyde, borax, polyethyleneimine, 3-aminopropyltriethoxysilane and (3-glycidylpropoxy)trimethoxysilane.

11. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The porous graphene oxide membrane further contains polymer nanomaterials; Preferably, the polymer nanomaterial includes one or more of cellulose nanofibers, cellulose nanocrystals, chitin nanofibers, chitin nanocrystals, chitosan nanofibers, chitosan nanocrystals, lignin nanofibers, and lignin nanocrystals. Preferably, the mass ratio of the polymer nanomaterial to the porous graphene oxide is (0.5-5):

1.

12. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The thickness of the porous graphene oxide film is 10-500 nm. And / or, the base membrane is an ultrafiltration membrane or a microfiltration membrane; And / or, the average pore size of the base film is 0.01-5 μm; And / or, the base film is made of one or more of nylon, polyethersulfone, polyvinylidene fluoride, polytetrafluoroethylene, cellulose acetate and polypropylene. And / or, the thickness of the base film is 50-200 μm.

13. The porous graphene oxide composite nanofiltration membrane according to claim 1, wherein, The porous graphene oxide composite nanofiltration membrane has a molecular weight cutoff of 1000-5000 Daltons, a rejection rate of ≥95% for reactive dyes, and a rejection rate of <12% for inorganic salts.

14. A method for preparing a porous graphene oxide composite nanofiltration membrane according to any one of claims 1-13, comprising the following steps: A mixture containing porous graphene oxide and a crosslinking agent is coated onto the surface of a base membrane to carry out a crosslinking reaction, forming a porous graphene oxide membrane, thus obtaining the porous graphene oxide composite nanofiltration membrane.

15. The method for preparing the porous graphene oxide composite nanofiltration membrane according to claim 14, wherein, The mixture containing porous graphene oxide and crosslinking agent further contains polymer nanomaterials; And / or, the content of porous graphene oxide in the mixture containing porous graphene oxide and crosslinking agent is 1-10 mg / mL; And / or, in the mixture containing porous graphene oxide and a crosslinking agent, the crosslinking agent accounts for 1-50% of the mass of the porous graphene oxide; And / or, the coating method includes one or more of blade coating, wire bar coating, slot coating and microgravure coating; And / or, a mixture containing porous graphene oxide and a crosslinking agent is coated onto the surface of a base film to form a wet film, the thickness of which is 5-100 μm; And / or, the crosslinking reaction is carried out at a temperature of 20-100°C for a time of 5 minutes to 48 hours.

16. The application of the porous graphene oxide composite nanofiltration membrane according to any one of claims 1-13 in the treatment of high-salt wastewater containing dyes and / or the desalination and purification of salt-containing dyes.

17. The application according to claim 16, wherein, The salt concentration in the high-salt wastewater containing dye is above 20 g / L, and the dye concentration is 0.1-5 g / L; And / or, the flux of the porous graphene oxide composite nanofiltration membrane for treating the high-salt wastewater containing dyes is 5-20 L / (m³). 2 (·h·Bar), dye retention rate is 95%-99.9%, desalination rate is <12%.

Citation Information

Patent Citations

  • Graphene oxide composite nanofiltration membrane and preparation method thereof

    CN110523297A

  • Graphene oxide composite nanofiltration membrane as well as preparation method and application thereof

    CN116020286A